2021
DOI: 10.1158/1940-6207.capr-21-0041
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide In Vitro Effects of Aspirin on Patient-derived Normal Colon Organoids

Abstract: Mechanisms underlying aspirin chemoprevention of colorectal cancer remain unclear. Prior studies have been limited because of the inability of preclinical models to recapitulate human normal colon epithelium or cellular heterogeneity present in mucosal biopsies. To overcome some of these obstacles, we performed in vitro aspirin treatment of colon organoids derived from normal mucosal biopsies to reveal transcriptional networks relevant to aspirin chemoprevention. Colon organoids derived from 38 healthy individ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…Network analyses have been used in research into other complex genetic traits to identify candidate genes involved in GWAS [43]. We have also previously made use of WGCNA to unravel the relationship between aspirin and CRC risk loci in colon organoids [15]. From our WGCNA, we identified candidate GWAS-related genes LARP4 and PIP4K2C as respective hub genes for the plum4 and lightsteelblue modules.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Network analyses have been used in research into other complex genetic traits to identify candidate genes involved in GWAS [43]. We have also previously made use of WGCNA to unravel the relationship between aspirin and CRC risk loci in colon organoids [15]. From our WGCNA, we identified candidate GWAS-related genes LARP4 and PIP4K2C as respective hub genes for the plum4 and lightsteelblue modules.…”
Section: Discussionmentioning
confidence: 99%
“…Genes rarely act in isolation, and expression of genes within related pathways are usually coordinated in such a way that they can be identified using systems level approaches. We have previously found that WGCNA led to the identification of modules driven both by aspirin-related genes and CRC loci in a similarly sized cohort of aspirin treated colon organoids [15]. Here, we generated a network of gene co-expression in our colon organoid model using WGCNA [31] and determined whether modules comprised within this network were differentially associated with carcinogens exposure (Supplementary Figure 2).…”
Section: Wgcna Reveals Altered Patterns Of Coexpression Following Carcinogen Treatmentmentioning
confidence: 98%
See 3 more Smart Citations